AR 2017
DOI: 10.21873/anticanres.11962
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Potential of Statins in Prostate Cancer Radiation Therapy

Abstract: Abstract. Background The management of prostate cancer is a significant healthcare challenge. Many treatment options exist (1-3), with radiation therapy playing a prominent role. However, the morbidity and cost of treatment are not trivial (4, 5). Although risk classification schemes (6) and nomograms (7) attempt to identify men most likely to benefit from treatment, it remains difficult to balance the risks of disease progression against competing risks of mortality (8). This has resulted in controversy over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…In combination with radiation, statins can improve clinical outcomes via their radiosensitizing properties. However, the available clinical data is conflicting ( 64 , 65 ). Here, upregulation of the Cholesterol Homeostasis gene set was associated with worse OS for CESC patients ( Figure 3H ; p= 0.012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In combination with radiation, statins can improve clinical outcomes via their radiosensitizing properties. However, the available clinical data is conflicting ( 64 , 65 ). Here, upregulation of the Cholesterol Homeostasis gene set was associated with worse OS for CESC patients ( Figure 3H ; p= 0.012).…”
Section: Resultsmentioning
confidence: 99%
“…An interesting finding was the upregulation of the Cholesterol gene set associated with OS in CESC patients. The Cholesterol pathway has been successfully targeted with statins, however combinations with radiotherapy resulted in conflicting results ( 64 ), which should be further unravelled.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding, the benefit of statin therapy particularly after diagnosis, is consistent with several large previous studies. With radio-sensitizing properties, statins have antitumor effects which support their beneficial use in prostate cancer 32. Raval et al33 performed a meta-analysis that included 34 observational cohort studies and found a 21% reduction in the risk of biochemical recurrence (BCR) in patients treated with statin and radiation therapy ( P =0.01).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, some studies have demonstrated a beneficial effect of statins in reducing PCa related mortality as well as overall PCa risk ( Katz et al, 2010 ; Marcella et al, 2012 ) whereas other studies have not revealed a significant effect ( Caon et al, 2014 ). Recently, conflicting data sourced from clinical outcomes obstruct the integration of neither beneficial nor harmful associations between the statin use and PCa ( Hutchinson and Marignol, 2017 ).…”
Section: Repurposed and Clinically Evaluated Non-cancer Drugs For Pcamentioning
confidence: 99%